The Role of the Audit Committee in Minimising Tax Avoidance Behaviour in Coal Mining Companies - Muhammad Aganthasyah; Kusharyanti, Kusharyanti; Januar Eko Prasetio (Proceeding International Conference on Accounting and Finance, 2025)
This study examines the role of the audit committee in minimizing tax avoidance practices in coal mining companies in Indonesia. Tax avoidance practices, although legal, are often controversial because they reduce the company's tax contribution to the state and create injustice among companies that comply with regulations. The mining sector, particularly the coal industry, is one of the sectors vulnerable to tax avoidance practices, particularly through transfer pricing methods and profit shifting to offshore affiliated entities. This study highlights the importance of strong corporate governance, particularly the presence of an independent and competent audit committee, in supporting corporate transparency and accountability. This study uses quantitative methods by observing 28 mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. Using multiple linear regression analysis, this study evaluates the effect of Audit committee attributes and controlariables such as Return on Assets (ROA) and Debt to Asset Ratio (DAR) on tax avoidance. The results show that the existence of an effective audit committee has a significant influence in reducing tax avoidance practices, while encouraging the implementation of better corporate governance and increasing compliance with tax regulations. These findings are expected to contribute to the development of stricter tax policies and support the improvement of the quality of corporate governance in sectors with a high risk of tax avoidance.